2008
DOI: 10.2215/cjn.01930408
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Atherosclerotic Calcification and Mo[Combining Diaeresis]nckeberg's Sclerosis

Abstract: Autopsy studies have demonstrated the near universal presence of fatty streaks and fibroatheromas in the general population from which patients with chronic kidney disease (CKD) arise. The vast majority of patients with CKD have multiple conventional cardiovascular risk factors. Vascular atherosclerotic calcification develops in most patients as they transition from the general population to significant CKD as part of cholesterol crystallization within atherosclerotic lesions. Once present, however, atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
109
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 64 publications
2
109
0
1
Order By: Relevance
“…Multiple pathways have been demonstrated to link CKD to inflammation and endothelial damage (21), including, but not limited to, a decreased clearance of proinflammatory cytokines (22), increased asymmetric dimethylarginine levels (6), and an increased oxidative stress (23). A previously reported accelerated development of atherosclerotic CVD (24) and vascular calcification (24) in uremia may also contribute. The target of ACE inhibition, angiotensin II, is itself an important inducer of vascular injury in several inflammatory settings other than uremia (25), where it induces endothelial dysfunction (25) and CRP generation (26), enhances vascular remodeling (25), and accelerates the progression of atherosclerosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pathways have been demonstrated to link CKD to inflammation and endothelial damage (21), including, but not limited to, a decreased clearance of proinflammatory cytokines (22), increased asymmetric dimethylarginine levels (6), and an increased oxidative stress (23). A previously reported accelerated development of atherosclerotic CVD (24) and vascular calcification (24) in uremia may also contribute. The target of ACE inhibition, angiotensin II, is itself an important inducer of vascular injury in several inflammatory settings other than uremia (25), where it induces endothelial dysfunction (25) and CRP generation (26), enhances vascular remodeling (25), and accelerates the progression of atherosclerosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between intimal and medial calcification is controversial and of interest in the nephrology community (10)(11)(12). Intimal and medial calcification are definitely related, have similar risk factors, and develop in parallel.…”
mentioning
confidence: 99%
“…Intimal and medial calcification are definitely related, have similar risk factors, and develop in parallel. Some have suggested that they are a continuum of vascular pathology (12). Clinically, it is difficult to differentiate them.…”
mentioning
confidence: 99%
“…Other limitations in this study are that we did not differentiate medial artery calcification, which is a common complication in ESRD patients 27 from atherosclerotic PAD.…”
Section: Discussionmentioning
confidence: 98%